LEARNING MODULE DEVELOPMENT ON COMPILING EXPOSITION AND ARGUMENTATION TEXT USING PROJECT-BASED LEARNING - Sakdiah Wati; Syafryadin Syafryadin; Eka Apriani (English Review: Journal of English Education, 2021)
This development research aims to develop and produce a learning module to compile an exposition text. Besides, this research and development also aim to describe the process of developing a material learning module, compiling an exposition text with a Project-Based Learning (PJBL) model for grade VIII SMP students, describing the feasibility of the module based on assessment and validation by media experts, material experts, linguists, and student trials. This research is included in the research category utilizing descriptive quantitative. The resulting quantitative data will be converted into qualitative data to describe the feasibility of the product being developed. The results of the research and development of the module show that the module developed is based on Tessmer's development with two main stages, namely the Preliminary stage which consists of the analysis and design stages, the Formative Evolution stage which consists of Self Evaluation, Prototyping, and Export Review. (Expert Test), One-To-One, Small Group, and Field Test. The validity of the learning module is seen based on the validation test, the results of the validation of media experts reach 75%, material experts 90%, and linguists 75% which can be categorized as valid. Based on product testing at the field test stage, the average score of students was 83.00 which could be categorized as good, while the results of the student response questionnaire obtained a score of 96% which could be categorized as very feasible. Based on the validation test, it can be concluded that the developed learning module can be used both in the student learning process independently and in the Indonesian language learning process, especially in the exposition text material of class VIII students in the class.